Manajemen Pengembangan Kinerja Pustakawan Perguruan Tinggi di Era Globalisasi Informasi Untuk Meningkatkan Mutu Layanan di Perpustakaan - Andi Ibrahim (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
The demanded of work quality of librarians based on career system and work achievement by giving reward and sanction is already mandated in UU No. 43 Tahun 1999 tentang Pokok-pokok Kepegawaian and its certainty is regulated in Kemenpan No. 132/KEP/M.PAN/12/2002 tentang Jabatan Fungsional Pustakawan dan Angka Kreditnya. Besides, librarians are expected to use each opportunity and are strong when facing any problem. To realize it, developing knowledge and skills is necessary. Such knowledge and skills must be relevance with librarian daily works and responsibilities. Moreover, self-development is also important to note. Self-development involved in motivation, behavior, profession, and individual characters that should be in librarians. By having such knowledge and skills, self-development as well, librarians will be advanced in services.